Etnomatematika Weti pada Sa’o di Kampung Adat Gurusina, Kabupaten Ngada, Provinsi Nusa Tenggara Timur - Yogasmara Binsar Putra Wimansyah; Ida Ayu Alit Laksmiwati; Ida Bagus Oka Wedasantara (Institut Nalanda, 2025)
Knowledge of symbolic meaning urine (carving) on sa'o(traditional house) in Gurusina Traditional Village has so far only been inherited by one traditional elder, so it is vulnerable to being cut off, especially after the major fire incident in 2018. This study aims to expand access to understanding the meaningurineand the ethnomathematical values ​​contained therein, which were previously only known by one individual. The approach used was qualitative with ethnographic methods, through observation techniques, interviews, literature studies, and document analysis. The results of the study showed thaturinecontains ethnomathematic elements that are not explicitly recognized as formal mathematical practices, such as the application of basic geometric forms, geometric elements, and geometric transformations. In addition to being an aesthetic expression,urinealso represents a cultural symbol that contains messages of life, moral values, and customary norms, functioning as ancestral advice in preserving cultural heritage. Thus,urineplay an important role in shaping cultural identity, collective consciousness, and passing on traditional values ​​to the younger generation of the Gurusina community.